Mobilization of impacted teeth in the digital age: a technical note - Scheurer, Carolien A. J.; Bouffleur, Frederic; Hodecker, Lutz; Lux, Christopher J.; Heberer, Marie-Therese; Mielke, Juliana (Quintessence international, 2025)
Objectives: Tooth mobilization is a challenging orthodontic treatment. Inadequate interdisciplinary communication between surgery and orthodontics, as well as limited knowledge of the topography of the surgical field, can lead to unfavorable positioning of the appliance. This can result in dangerous force vectors for tooth movement. Comprehensive digital planning and customized tools could reduce these sources of error. Two cases of impacted canines were treated using cutting guides and customized attachments. - Method and materials: A CBCT and intraoral scan were taken for planning. A CAD process was used to design a cutting guide and a customized attachment according to the required force vectors (OnyxCeph3, Image Instruments). Using various CAM processes, the cutting guide (BioMed Clear Resin, Formlabs) and a customized attachment dummy (Permanent Crown Resin, Formlabs) were fabricated in a 3D printer (Form 3B, Formlabs). The customized attachment was fabricated from titanium using the selective laser melting process (OrthoLIZE). The teeth were surgically exposed using the cutting guide and customized attachment dummies. The customized attachment was conventionally cemented using Transbond XT (3M Unitek). - Results: All teeth were successfully exposed with the cutting guides. The customized attachments could only be placed in the predetermined position according to the digital planning. - Conclusion: The 3D planned cutting guide can help to shorten the surgical procedure and keep the surgical field as small as possible. The 3D planned customized attachment allows precise positioning. The digitally planned force vectors should prevent side effects on adjacent teeth and allow targeted mobilization. However, studies are needed for further validation.